2012
DOI: 10.7314/apjcp.2012.13.6.2495
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Nasopharyngeal Carcinoma Mortality in China, 1973-2005

Abstract: The trend was similar in both men and women, in both urban and rural areas, but the declining rates in females were more remarkable than in males. The mortality rates were higher for the age groups above 50 years than those less than 50 years of age, both showing downward trend over 30-year period. In summary, the overall NPC mortality has consistently decreased in China over the past three decades, particularly in women and in old adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…(Wided et al, 2015) Importantly, along with the declining incidence of NPC, the mortality rate has also declined. (Huang et al, 2012) The declining rates observed in our studies, consistent with what have been generally reported elsewhere are accounted for by several important factors. In Brunei, the most important factor is perhaps the improvement in the standards of living; decline in reliance on firewood resulting in less exposure to smoke, consumption of less salted preserved meats and also consumption of more fresh produces (vegetables and fruits).…”
Section: Discussionsupporting
confidence: 81%
“…(Wided et al, 2015) Importantly, along with the declining incidence of NPC, the mortality rate has also declined. (Huang et al, 2012) The declining rates observed in our studies, consistent with what have been generally reported elsewhere are accounted for by several important factors. In Brunei, the most important factor is perhaps the improvement in the standards of living; decline in reliance on firewood resulting in less exposure to smoke, consumption of less salted preserved meats and also consumption of more fresh produces (vegetables and fruits).…”
Section: Discussionsupporting
confidence: 81%
“…The decrease in mortality is mainly caused by that in the incidence rate. This trend is the same as in China, 1973(Huang et al, 2012.…”
Section: Discussionsupporting
confidence: 63%
“…A study conducted in Chinese-Americans living in Los Angeles County and the San Francisco metropolitan area also showed a decreased rate among men from 1992 to 2002, with the overall decline limited primarily to type I tumours, which are moderately differentiated squamous cell carcinomas (Sun et al, 2005). From 1973 to 2005, there was also a general trend of decrease in NPC mortality in both men and women in China (Huang et al, 2012). However, a similar study conducted over a 20-year period (1978-2002) in Sihui and Cangwu (Sihui county is located in the middle east part of Guangdong province, and Cangwu county is located in Guangxi province at the border between Guangxi and Guangdong) found stable incidence rates (Jia et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…
Asian Pac J Cancer Prev, 15 (17), [7459][7460][7461][7462][7463][7464][7465] Introduction Nasopharyngeal carcinoma (NPC) is a common head and neck malignant neoplasm, especially in southern China where the major pathological type of NPC is nonkeratinizing undifferentiated carcinoma (World Health Organization Type III) (Jemal et al, 2011;Huang et al, 2012). Several factors have been proved to enhance the risk of NPC, including Epstein-Barr virus (EBV), smoking, alcohol consumption, salt-preserved foods and family history of cancer, etc (Chien et al, 2001;Jia et al, 2010;Ji et al, 2011;Hashim et al, 2012).

Extensive investigations have showed that the ABO blood group might be associated with risk to certain malignancies (Iodice et al, 2010;Gates et al, 2011;Joh et al, 2012;Wang et al, 2012;Zhang et al, 2014).

…”
mentioning
confidence: 99%